Modeling Artificial Life Through Multi-Agent Based Simulation - Ruas, Terry Lima; Marietto, Maria das Graças Bruno; Batista, André Filipe de Moraes; França, Robson dos Santos; Heideker, Alexandre; Noronha, Emerson Aguiar; Silva, Fábio Aragão da (IntechOpen, 2011)
None